2022
DOI: 10.3389/fneur.2022.1046351
|View full text |Cite
|
Sign up to set email alerts
|

Stroke systems of care in the Philippines: Addressing gaps and developing strategies

Abstract: In the Philippines, the mortality from stroke during the last 10 years remains high. This paper aims to describe the gaps in stroke care and the development of stroke systems of care in the Philippines. Gaps in stroke systems of care include low number of neurologist, inadequate CT scan machines, lack of stroke training among health workers, lack of stroke protocols and pathways, poor community stroke awareness, low government insurance coverage with high out of pocket medical expenses, lack of infrastructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Furthermore, we noted that the AAPC of age-standardized metrics showed an increasing trend in Philippines in Southeast Asia. A study found that stroke mortality in Philippines has remained high over the past decade, which is similar to our findings ( 29 ). In low- and middle-income countries, dietary patterns are changing considerably, such as the replacement of staple-based diets with increased fat, meat and salt intakes ( 30 ).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we noted that the AAPC of age-standardized metrics showed an increasing trend in Philippines in Southeast Asia. A study found that stroke mortality in Philippines has remained high over the past decade, which is similar to our findings ( 29 ). In low- and middle-income countries, dietary patterns are changing considerably, such as the replacement of staple-based diets with increased fat, meat and salt intakes ( 30 ).…”
Section: Discussionsupporting
confidence: 92%
“…Two reviews are included in this scoping review. One review on neurocritical care was published in 2022 and explores the current shortcomings in the management of stroke care and the subsequent courses of action to augment these gaps 49 . The second review was published in 1995 and gave an overview of the state of Philippine emergency medicine at the time 2 .…”
Section: Discussionmentioning
confidence: 99%
“…One review on neurocritical care was published in 2022 and explores the current shortcomings in the management of stroke care and the subsequent courses of action to augment these gaps. 49 The second review was published in 1995 and gave an overview of the state of Philippine emergency medicine at the time. 2 It provided information regarding the existing emergency medicine training programs, EDs, EMS systems, emergency physicians, and research.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, stroke is a leading cause of mortality and disability 1. The prevalence of stroke in the Philippines ranges from 0.5% to 1.9%, with age-standardized mortality of 82.8 per 100,000 person-years 2–6. In 2017, it ranks as the second most common cause of death after heart disease in the country.…”
mentioning
confidence: 99%
“…1 The prevalence of stroke in the Philippines ranges from 0.5% to 1.9%, with age-standardized mortality of 82.8 per 100,000 person-years. [2][3][4][5][6] In 2017, it ranks as the second most common cause of death after heart disease in the country. The stroke burden in terms of age-standardized and sex-standardized disability-adjusted life years lost is 2171/100,000 people.…”
mentioning
confidence: 99%